2008
DOI: 10.1128/jcm.02255-07
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of New Staphylococcal Cassette Chromosome mec (SCC mec ) and Topoisomerase Genes in Fluoroquinolone- and Methicillin-Resistant Staphylococcus pseudintermedius

Abstract: Fluoroquinolone-and methicillin-resistant Staphylococcus pseudintermedius isolates harbor two new staphylococcal cassette chromosome mec (SCCmec) elements that belong to class A, allotype 3 (SCCmec II-III), and to the new allotype 5 (SCCmec VII). Analysis of the complete nucleotide sequences of the topoisomerase loci gyrB/gyrA and grlB/grlA revealed mutations involved in fluoroquinolone resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
139
0
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(154 citation statements)
references
References 28 publications
10
139
0
5
Order By: Relevance
“…This is in line with recent studies showing the acquisition of resistance genes by incorporation of mobile elements in the genome (7). Furthermore, in the very successful CC71 lineage, SCCmec types II and III predominate (15,28), but other types are emerging (7,29).…”
Section: Discussionsupporting
confidence: 72%
“…This is in line with recent studies showing the acquisition of resistance genes by incorporation of mobile elements in the genome (7). Furthermore, in the very successful CC71 lineage, SCCmec types II and III predominate (15,28), but other types are emerging (7,29).…”
Section: Discussionsupporting
confidence: 72%
“…Investigations of resistance mechanisms and their distribution among staphylococcal populations have been conducted, but further work is needed to fully evaluate their clinical relevance. 3,9 The current study and others also confirm that relative resistance of S. pseudintermedius to oxacillin has increased in recent years. 10,13,15,19,20 Efforts to standardize detection methods, establish shared databases, promote collaborative research, and create venues for sharing knowledge of MRSP will help improve surveillance and reduce the spread of MRSP.…”
Section: Discussionsupporting
confidence: 67%
“…According to Clinical and Laboratory Standards Institute (CLSI) guidelines, MIC cutoff values for oxacillin for determining methicillin resistance against S. aureus and S. lugdunensis are 4 g/ml and differ from the values for other species (0.5 g/ml) (8). It was previously reported that some strains exhibited oxacillin MICs of 0.5 to Ͻ4 g/ml among mecA-positive S. pseudintermedius strains (4,9,27). If such strains are not identified as S. pseudintermedius strains but are identified as S. aureus strains, they could be misidentified as being methicillin-susceptible strains.…”
Section: Discussionmentioning
confidence: 99%